Influence of Intraradicular post Lengths and Surface characteristics on Fracture Resistance of Endodontically Treated Teeth - Hend Elkawash; Milad Eshah (Khalij-Libya Journal of Dental and Medical Research, 2022)
Objectives. The purpose of this in vitro study was to evaluate the fracture resistance of endodontically treated teeth that were prosthetically restored with two fiber post Surface characteristics with different lengths (8,10 and 12mm). Material and methods. A total of thirty intact upper central incisors were collected and decoronated 2mm above to the cemento –enamel junction. Then prepared with 2mm a circumferential ferrule and a chamfer finish line of 0.5 mm. The teeth were embedded in epoxy resin blocks using a centralizing device. Root canals were performed then post holes were prepared with the corresponding drill using the drilling machine. The thirty samples were divided into 2 main groups according to the post surface characteristics Group І: parallel smooth glass fiber post. (n=15). Group ІІ: parallel serrated glass fiber post. (n=15). The samples of each group were further subdivided into three sub-groups(n=5) according to different post lengths as follows: Sub Group A: 8mm length. Sub Group B: 10 mm length. Sub Group C:12mm length. All posts were cemented with a-self-adhesive resin cement using a load applicator device. Metal crown coping was constructed and cemented to the post and core assembly. Each specimen was then subjected to a compressive test in a universal testing machine where load was applied on palatal side at angle of 135 degrees in relation to long axis of the root at across head speed of 1mm/min until failure occurred. Results. There was no statistically significant difference between the tested post Surface characteristics, and there was a statistically significant difference between the three post lengths. Conclusion. The increased in post length showed significant increase fracture resistance of endodontically treated maxillary central incisor teeth, while Surface characteristics of post showed non-significant influence to fracture resistance. Citation: Elkawash H, Eshah M. Influence of Intraradicular post Lengths and Surface characteristics on Fracture Resistance of Endodontically Treated Teeth. Khalij-Libya J Dent Med Res. 2022;6(2):144–151. https://doi.org/10.47705/kjdmr.226209